Experimental test on polyended polysterene addition as a partial substitute of fine aggregate - Bagas Habibilah; Slamet Widodo (Journal of Engineering and Applied Technology, 2022)
This research aimed to determine the values of specific gravity, compressive strength, and modulus of elasticity by replacing some fine aggregate with styrofoam (Polyended Polysterene). This research was done by using experimental methods in the Building Materials Laboratory, Department of Civil and Planning Engineering Education, Universitas Negeri Yogyakarta. The percentage of Polyended Polysterene addition as a partial substitute of fine aggregate was done at 0%, 15%, 30%, and 45%. Each percentage of Polyended Polysterene addition as a partial replacement of fine aggregate consisted of 3 cylindrical concrete specimens with a diameter of 150 mm and a height of 300 mm. Specific gravity testing of concrete was conducted 24 hours after concrete casting. The compressive strength and modulus of elasticity of the concrete were tested at 91 days. The results of the research showed that: (1) the specific gravity values of concrete decreased linearly with the value of 2345,83 kg/m3, 2242,45 kg/m3, 2154,88 kg/m3, and 2040,79 kg/m3, (2) the compressive strength values of concrete are 28,55 MPa, 18,52 MPa, 20,26 MPa, and 15,3 MPa, and (3) the modulus of elasticity values of concrete is 15969,61 MPa, 13395,58 MPa, 14994,2 MPa, dan 14479,03 MPa. From the test results, the optimal value at a percentage of 30% with a specific gravity value of concrete close to the lightweight concrete requirements and a compressive strength value meets the structural requirements.